FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN MAKANAN SISWA SEKOLAH MENENGAH ATAS DI KOTA YOGYAKARTA - Indira Putuayu Septiani; Herawati Herawati; A Fahmy Tsani (Poltekkes Kemenkes Maluku, 2017)
The problem of nutrient in take in teenagers tends to be caused by a poor and irregular diet as well as psychosocial factors involved frequently become the cause of this matter. This research is aimed to determine the factors associated with food selection in high school students in Yogyakarta City. The design of this research was observational, with crosssectional design on 2 high schools in Yogyakarta City. The sampling was done by simple random sampling. A sample of 107 students was examined as the sample. The variable examined in this research wasthe role of the family, peers,pocket money, the level of knowledge and mood towards food selection. The data were analyzed by using chi-square. Factors significantly related(p <0.05) to the food selection is the role of the family in the selection of staple foods, side dishes from animal products, side dishes from vegetables, vegetables and fruits. The significant relationshipis also found at the level of knowledge with food selection of vegetables and fruits. In addition, a significant relationship between mood and selection of staple foods and side dishes from animal products is also found. Meanwhile, there is no significant relationship between pocket money and the role of peers towards all types of food selection. The role ofthe family, the level of knowledge and mood are related to food selection, while pocket money and peers are not related to food selection. Keywords : Food selection, teenagers